2018
DOI: 10.31073/zem.95.78-81
|View full text |Cite
|
Sign up to set email alerts
|

Regime of soil humus rural residential areas organic farming systems

Abstract: The changes of the soil’s humus soil within the rural areas are investigated for the organic farming system. The most significant impact of organic agriculture on humus content over 55% was observed on soddy podzolic soils (V>75%), the lowest –7,5% on typical chernozem (V≈16%). Changes in the qualitative composition of humus for the introduction of various types of organic substrates are analyzed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…L. Shkarivska et al (2021), scientists of the NSC "Institute of Agriculture of the National Academy of Sciences of Ukraine" also assure that it is possible to use digestates as fertilizers, but it is necessary to control the presence of heavy metals and trace elements in them, because thanks to the agrochemical examination of digestates and their by-product (liquid fraction) a high their nutrient content. Some laboratory studies have confirmed significant reductions in N 2 O emissions when using nitrification inhibitors in the digestate (Wolf et al, 2014;Severin et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…L. Shkarivska et al (2021), scientists of the NSC "Institute of Agriculture of the National Academy of Sciences of Ukraine" also assure that it is possible to use digestates as fertilizers, but it is necessary to control the presence of heavy metals and trace elements in them, because thanks to the agrochemical examination of digestates and their by-product (liquid fraction) a high their nutrient content. Some laboratory studies have confirmed significant reductions in N 2 O emissions when using nitrification inhibitors in the digestate (Wolf et al, 2014;Severin et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…L. Shkarivska et al (2021), scientists of the NSC "Institute of Agriculture of the National Academy of Sciences of Ukraine" also assure that it is possible to use digestates as fertilizers, but it is necessary to control the presence of heavy metals and trace elements in them, because thanks to the agrochemical examination of digestates and their by-product (liquid fraction) a high their nutrient content.…”
Section: Fertilizer Application Rate T/ Ha (Factor A)mentioning
confidence: 99%